Effect of explosive-based training on musculotendinous stiffness and running economy in highly-trained distance runners - Williams, J. A. (Journal of Australian Strength and Conditioning, 2020)
Strength and Power training modalities continue to emerge amongst elite-level endurance athletes. Despite common misconceptions surrounding such training, enhancements in overall running performance, most notably Running Economy, has the ability for individuals to overcome their competitors. A total of seven original experimental articles were used for this review. The primary finding from this review was that endurance performance characteristics, specifically Running Economy, were enhanced after participating in strength and power-based training (2-8%). Improvements in Rate of Force Development with a concomitant decreased demand for oxygen at a given speed showed improvements in time trials and time to exhaustion. Differing magnitudes of results may be due to subjects previous history, exercise selection, volume load and testing protocols. There was shown to be a lack of direct measurement for the stiffness and/or compliance qualities of the Musculotendinous Unit from the studies chosen. Strength and Power based training has the potential to elicit positive enhancements in performance characteristics amongst elite-level endurance athletes. The use of multi-joint explosive exercises such as unloaded and loaded jump squats, scissor jumps, bounding, and wall sprints are recommended as they closely resemble running mechanics. Programming factors such as progressive overload, work:rest ratio, training frequency and intensity must be individualised appropriately in order to maximise training adaptations and limit accumulative fatigue. Based on the reviewed studies, elite distance runners are recommended to engage in specific explosive strength training 2-3 days per week for 8-12 weeks in order to improve overall running performance (decreased energy expenditure and oxygen demand at particular velocities).